Urbanization and emerging mental health issues - Ventriglio, Antonio; Torales, Julio; Castaldelli-Maia, João M.; De Berardis, Domenico; Bhugra, Dinesh (CNS spectrums, 2021)
Rapid urbanization worldwide is associated to an increase of population in the urban settings and this is leading to new emerging mental health issues. This narrative mini-review is based on a literature search conducted through PubMed and EMBASE. A total of 113 articles published on the issue of urban mental health have been selected, cited, reviewed, and summarized. There are emerging evidences about the association between urbanization and mental health issues. Urbanization affects mental health through social, economic, and environmental factors. It has been shown that common mental syndromes report higher prevalence in the cities. Social disparities, social insecurity, pollution, and the lack of contact with nature are some of recognized factors affecting urban mental health. Further reserach studies and specific guidelines should be encouraged to help policy makers and urban designers to improve mental health and mental health care facilities in the cities; additional strategies to prevent and reduce mental illness in the urban settings should be also adopted globally.